Indazole-derived synthetic cannabinoids: Absolute configuration determination and structure characterization by circular dichroism and DFT calculations - Dobšíková, K; Spálovská, D; Kuchař, M; Paškanová, N; Setnička, V (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2023)
An increasing number of products containing synthetic cannabinoids pose a growing crisis to public health worldwide. Recently, a rising number of cases of serious adverse health effects, intoxications, and death cases associated with synthetic cannabinoids were reported. The current study represents the comprehensive structural analysis of three new synthetic cannabinoids (AB-, ADB- and AMB-FUBINACA) in solution investigated by electronic and vibrational circular dichroism together with the conventional methods of infrared and ultraviolet absorption spectroscopy, all supported by the density functional theory (DFT) calculations. The best level of theory to reproduce the experimental wavenumbers and wavelengths was found to be the B3PW91 method with a 6-311++G(d,p) basis set including the implicit solvent effect simulation. Very good agreement between the experimental and simulated spectra allowed us to determine the absolute configuration and a detailed interpretation of the IR absorption, VCD, ECD and UV spectra of AB-, ADB- and AMB-FUBINACA. In addition, the HOMO and LUMO electronic transitions were calculated.
Keywords: Cannabinoids; teorie funkcionálu hustoty; kanabinoidy; Density Functional Theory; Chiroptical spectroscopy; DFT calculation; Drugs; Vibrational spectroscopy; Synthetic cannabinoids; cirkulární dichroismus; Circular Dichroism